Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) untuk Menghindari Resiko Kecelakaan Kerja di PT.PP London Sumatra Indonesia Tbk Begerpang Palm Oil Mill - Mika Sri Wahyuni (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
PT.PP London Sumatra Indonesia Tbk combines the objectives of occupational safety and health into the management system at all levels of the company. Management is responsible for preventing injuries and diseases due to work. PT.PP London Sumatra Indonesia Tbk has succeeded in implementing an occupational safety and health management system to minimize work accidents. The occupational safety and health management system program has been established in oil palm factory in the form of recruitment, education and training, counseling, use of personal protective equipment and appreciation. Evaluation of the P2K3 work program on K3 policy can produce results, namely the acquisition of zero accident in the palm oil mill environment, in the factory environment there are no work accidents that cause loss of employee working days. The influence and application of SMK3 can be proven from the lack of work accidents in the palm oil mill environment, and several awards are obtained about occupational safety. PT. PP London Sumatra Indonesia, Tbk was given a zero accident award for its achievements in implementing the Occupational Safety and Health Program (K3) so as to reach 2,596,288 working hours of people without work accidents, starting from January 1, 2012 to March 31 2016. Then won a gold flag award in SMK3 in Begerpang POM in 2009 and 2012. In the framework of implementing Government No. 50 of 2012 concerning the application of SMK3 in the workplace.